Searching for Motivation. An exploration of why tourists travel to Alta, guided by NordNorsk Reiseliv’s Travel Styles. - Langhelle, Ingrid Birknes (UiT The Arctic University of Norway, 2020)
This thesis explores the topic of motivation and what motivates tourists to travel. The specific focus is on Alta, why people travel there and what motivates them to pick different travel experiences within the destination. NordNorsk Reiseliv’s Travel Styles have been used as a framework for this investigation and this thesis also explores the usefulness of this kind of categorisation of tourist. Data collected from two popular tourism companies in Alta is weighed against the theory relating to tourist motivation and typologies in general. The usefulness of the Travel Styles are explored, alongside the reasons people make the choices that they make, both in terms of travel destination and experiences. The aim is to gain a better understanding of the tourists that travel to Alta and test an important tool that is being implemented in the tourism industry across Northern Norway. The results show that while the Travel Styles can be useful for certain purposes, as is the case with many other typologies, they fail to grasp the complexity of why people travel. The reasons people make the choices that they do is layered and these layers are some of the things that are being detailed in the findings. Keywords: Motivation, Travel Styles, Alta, Typologies, Winter tourism.